TROPICAL FRUITS OF MANGO AND NONI HAVING DUAL EFFECTS OF COAGULATING MILK AND ENRICHING THE CURDS WITH MICRO-CONSTITUENTS OF MEDICINAL POTENTIAL - Vejayan, Jaya; Munir, Norliana; Lee Lian, Yee; Bathmanathan, Rupbansraaj; Ibrahim, Halijah; Chakravarthi, Srikumar (Malaysian Journal of Science, 2019)
Plants are capable of coagulating milk efficiently and enriching the curd with medicinal potentials, which can result in an ideal functional dairy food. Such efforts were attempted within this study with two fruit bearing plants, Mango (Mangifera indica) and Noni (Morinda citrifolia). The extracts of the two plants were separated to their enzymatic fractions and investigated for their coagulating time in comparison to rennet enzyme of Mucor miehei. The biological activities of the curd formed by the extracts were evaluated to determine the antioxidant and antidiabetic activities. The coagulation of milk by M. indica seed fraction, M. citrifolia fruit fraction and the rennet (15%, 15%, and 5% (w/v), respectively) resulted in coagulation times of 10.8 ± 0.36 s, 40.73 ± 1.91 s and 198.2 ± 1.01 s, respectively. Curd by aqueous extract of M. indica seeds resulted in the most favourable values: IC50 = 3.266 ± 0.353 μg/mL (2,2-diphenyl-1-picylhydrazyl, DPPH), 147.329 ± 1.890 mg GAE/g (Ferric Reducing Antioxidant Power, FRAP), IC50 = 17.87 ± 0.415 μg/mL (α-glucosidase inhibition) and IC50 = 41.87 ± 0.585 μg/mL (α-amylase inhibition). Hence, M. indica seed and M. citrifolia fruit extracts were tested, and both plant extracts, together with curd-fortification, exhibited useful biological activities.